Aplikasi Regresi Data Panel: Determinan Kualitas Lingkungan Hidup di Indonesia Tahun 2019-2023 - Jonatan, Hotton; Salam, Rudi (Seminar Nasional Official Statistics, 2025)
The Environmental Quality Index (IKLH) is an indicator used to measure environmental development in Indonesia. Nationally, IKLH showed an increasing trend from 2019 to 2023. However, Indonesia's Environmental Performance Index (EPI) in 2024 was only 33.6, ranking 163rd out of 180 countries, reflecting poor environmental quality by global standards. This study analyzes the factors affecting IKLH using panel data regression from 2019 to 2023. The variables include population density, GRDP per capita, energy consumption, and the percentage of the poor population. The results indicate that population density, GRDP per capita, and energy consumption have a significant negative effect on IKLH, while the percentage of the poor has a positive but insignificant effect. These findings highlight that economic and demographic pressures are key contributors to declining environmental quality. Hence, sustainable control of economic activities and population growth, along with integrated environmental policy reforms, is essential.